Motivasi Peternak Sapi Terhadap Usaha Ternak Sapi Potong Di Pulau Moa Kabupaten Maluku Barat Daya - Nontjie Haumahu; George S.J. Tomatala; Pieter M Ririmasse (JURNAL PERTANIAN KEPULAUAN, 2020)
The research aimed to investigate the motivation of cattle herders in Moa District, Southwest Maluku Regency. Three villages, namely Tounwawan, Klis, and Werwaru, and thirty respondents were selected using the purposive sampling method based on population and cattle ownership. The results showed that the overall economic motive was the strongest (99.6%) compared to social motive (98.58%) and entertainment motive (95.06%). Motivation levels ranging from middle (80,6% of respondents) to high (19,4% of respondents). The regression test R square = 0.099 with regression equation Y= 3.629 + 0.003 XI + 0.018X2 -0.016X3 + 0.002X4 + 0.006X5. It was concluded that the cattle herders were pushed dominantly by economic motives than social and entertainment motives. Age, education, dependency, experience, and cattle ownership have no significant effect on the motivation of the cattle herders.